THE EFFECT OF EXTERNAL ENVIRONMENT AND FIRM SIZE ON THE RELATIONSHIP BETWEEN KNOWLEDGE MANAGEMENT AND COMPETITIVE ADVANTAGE - Kimani, George Kinyanjui; Ogutu, Professor Martin (European Journal of Business and Strategic Management, 2018)
The purpose of this study was to investigate the effect of external environment and firm size on the relationship between knowledge management and competitive advantage. Empirical literature indicates that the external environment of an organization has an impact on an organization's effectiveness, efficiency; relevance and financial viability with higher impacts on the relevance performance indicators. Studies on the effect of firm size on firm competitive advantage have generated mixed results ranging from those supporting a positive relationship among these variables to those opposing it. Larger firms are less productive but more profitable. The absolute firm size plays an important role in explaining profitability.Empirical results show that there is a positive correlation between knowledge management and competitive advantage knowledge acquisition, knowledge storage, knowledge creation, knowledge sharing, and knowledge implementation have significant factor loading on knowledge management; and also productivity, financial performance, staff performance, innovation, work relationships, and customer satisfaction have significant factor loading on organizational performance. Results also suggest that knowledge management practices directly influence the organizational performance. Effective knowledge management plays an increasingly important role in sustaining the competitive advantage of firms in the new economy. Competitive advantage is brought about through developing and putting into effect innovative business solutions that recycle applicable knowledge. Contextual gaps exists as most of the studies mainly explored the context of advanced, developed countries while, at the same time, little empirical evidence has been found in investigating a dynamic capability view of knowledge management. Future studies should attempt to establish whether the propositions stated in this paper hold empirically. In addition, future studies should also attempt to establish the nature of relationship between Knowledge management, external environment and competitive advantage. Is the relationship direct and significant, indirect-intervening or indirect- moderating? Future studies can help to conclude on these questions. Keywords: Knowledge management, external environment, firm size, organizational performance, competitive advantage